The Ludic Logic of Tragedy. (3rd July 2016) - Rokem, Freddie
Abstract : Logical argumentation and reasoning have been embedded in tragedies, beginning already two generations before Aristotle formulated the principles of logic. Therefore, these logical principles can also be extracted from tragedies, here exemplified by examining Sophocles'Antigone andOedipus Tyrannus . Looking more closely at the 'use' of logic in these plays—in particular the use of deductive syllogism and the law of contradiction—the article draws attention to the fact that logical reasoning often collapses and is even subverted, in particular in contexts where someone attempts to define what it means to be human. While rationality and logic are seen as the defining characteristic of being human in philosophical contexts, the theatrical uses of logic contradicts and even subverts this logic, by logical means. Arguing with rational means that there is something contradictory (and irrational) in human nature creates a paradoxical situation on which what I term the 'ludic logic of tragedy' is based.